How do you differentiate #-2y=x-cosy/(xy)#?
By signing up, you agree to our Terms of Service and Privacy Policy
To differentiate the given function ( -2y = x - \frac{\cos(y)}{xy} ) with respect to (x), we'll use the quotient rule and the chain rule:
[ \frac{d}{dx}(-2y) = \frac{d}{dx}\left(x - \frac{\cos(y)}{xy}\right) ]
[ -2\frac{dy}{dx} = 1 - \frac{d}{dx}\left(\frac{\cos(y)}{xy}\right) ]
[ -2\frac{dy}{dx} = 1 - \frac{xy\frac{d}{dx}(\cos(y)) - \cos(y)\frac{d}{dx}(xy)}{(xy)^2} ]
[ -2\frac{dy}{dx} = 1 - \frac{xy(-\sin(y)\frac{dy}{dx}) - \cos(y)(y\frac{dx}{dx} + x\frac{dy}{dx})}{(xy)^2} ]
[ -2\frac{dy}{dx} = 1 - \frac{-xy\sin(y)\frac{dy}{dx} - xy\cos(y) - xy^2\frac{dy}{dx}}{(xy)^2} ]
[ -2\frac{dy}{dx} = 1 - \frac{-xy\sin(y)\frac{dy}{dx} - xy\cos(y) - xy^2\frac{dy}{dx}}{x^2y^2} ]
[ -2\frac{dy}{dx} = 1 + \frac{xy\sin(y)\frac{dy}{dx} + xy\cos(y) + xy^2\frac{dy}{dx}}{x^2y^2} ]
[ -2\frac{dy}{dx} = 1 + \frac{xy(\sin(y)\frac{dy}{dx} + \cos(y) + y^2\frac{dy}{dx})}{x^2y^2} ]
[ -2\frac{dy}{dx} = 1 + \frac{xy(\sin(y) + y^2)\frac{dy}{dx} + xy\cos(y)}{x^2y^2} ]
[ \frac{dy}{dx} = \frac{1 + \frac{xy\cos(y)}{x^2y^2}}{-2 - \frac{xy(\sin(y) + y^2)}{x^2y^2}} ]
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- How do you differentiate #f(x)=1/cossqrt(lnx)# using the chain rule?
- How do you differentiate # y= 3y^4-4u+5 ;u=x^3-2x-5 # using the chain rule?
- How do you differentiate #f(x) = ( 4x - 3) ( xe^x)# using the product rule?
- How do you implicitly differentiate #-y^2=e^(y)-y/x #?
- How do you differentiate #f(x)=csc(ln(1-x^2)) # using the chain rule?
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7